Efficient Indexing and Searching of Big Data in HDFs - Deepika, D; Pugazhmathi, K (International Journal of Computer Sciences and Engineering, 2025)
Efficient indexing is an efficient, standard data structure, most suited for look operation over an exhaustive set of data. The enormous set of data is mostly unstructured furthermore, does not fit into traditional database categories. Extensive scale preparing of such data needs a dispersed structure such as Hadoop where computational assets could easily be shared furthermore, accessed. An execution of a look motor in Hadoop over millions of Wikipedia reports utilizing an transformed record data structure would be conveyed out for making look operation more accomplished. Transformed record data structure is utilized for mapping a word in a record or set of records to their relating locations. A hash table is utilized in this data structure which stores each word as record furthermore, their relating areas as its values thereby providing simple lookup furthermore, extremely of data making it suitable for look operations.